Bilateral optic neuropathy following bite from brown recluse spider (Loxosceles reclusa). (2nd April 2016) - Mantopoulos, Dimosthenis; Hendershot, Andrew J.; Cebulla, Colleen M.; Hirsh, David K.
Abstract: A 63-year-old female with history of a resected frontal lobe meningioma presented with bilaterally decreased vision after a bite from a brown recluse spider. The exam was significant for a left relative afferent pupillary defect, bilateral optic nerve pallor, decreased foveal sensitivity in the left eye and new bilateral visual field defects, despite stability of her meningioma. The findings remained stable at 1-year follow-up. To our knowledge, this is the first reported case of optic neuropathy secondary to a brown recluse spider bite. Visual field tests performed prior to the bite allowed us to compare and localize changes related to the bite.